Expression pattern of synaptic vesicle protein 2 (SV2) isoforms in patients with temporal lobe epilepsy and hippocampal sclerosis. Issue 2 (February 2014) - Crèvecœur, J.; Kaminski, R. M.; Rogister, B.; Foerch, P.; Vandenplas, C.; Neveux, M.; Mazzuferi, M.; Kroonen, J.; Poulet, C.; Martin, D.; Sadzot, B.; Rikir, E.; et al.
<x xml:space="preserve">Abstract</x> Aims Synaptic vesicle proteins 2 (SV2) are neuronal vesicles membrane glycoproteins that appear as important targets in the treatment of partial and generalized epilepsies. Therefore, we analysed the expression of SV2 isoforms in the hippocampus of patients with temporal lobe epilepsy (TLE). Methods SV2A, SV2B and SV2C immunostaining and QuantiGene branched DNA assay were performed on biopsies from 31 consecutive TLE patients with mesial temporal sclerosis (MTS) and compared with 10 autopsy controls. SV2 expression was further compared with Timm's staining, and synaptophysin, Zinc transporter 3 (ZnT3), dynorphin, vesicular glutamate transporter 1 (VGLUT1) and vesicular GABA transporter (VGAT) expression. Results In TLE patients, SV2A and SV2B expression was decreased in areas of synaptic loss. SV2C, which is weakly expressed or absent in the hippocampus of controls, was overexpressed in 10/11 cases with classical MTS1A and mossy fibre sprouting but not in cases with other types of MTS. SV2C staining was located in the inner molecular layer of the dentate gyrus and colocalized with dynorphin, ZnT3 and VGLUT1, suggesting selective expression in presynaptic glutamatergic Zn2+‐rich terminals of abnormal sprouting fibres. SV2 expression patterns correlated with histological subtypes of MTS, but not with clinical features or therapeutic regimens in this patient cohort. Conclusion In classical MTS1A, the expression of SV2 isoforms is altered with a marked decrease of SV2A and SV2B paralleling synaptic loss and a selective increase of SV2C in sprouting mossy fibres. These findings suggest a different physiology of sprouting synapses and the possibility to target them with SV2C‐specific strategies.